Fas Apoptosis Inhibitory Molecule Blocks and Dissolves Pathological Amyloid-β Species - Kaku, Hiroaki; Ludlow, Alexander V.; Gutknecht, Michael F.; Rothstein, Thomas L. (Frontiers in Molecular Neuroscience, 2021)
A number of neurodegenerative diseases are associated with the accumulation of misfolded proteins, including Alzheimer’s disease (AD). In AD, misfolded proteins such as tau and amyloid-β (Aβ) form pathological insoluble deposits. It is hypothesized that molecules capable of dissolving such protein aggregates might reverse disease progression and improve the lives of afflicted AD patients. Here we report new functions of the highly conserved mammalian protein, Fas Apoptosis Inhibitory Molecule (FAIM). We found that FAIM-deficient Neuro 2A cells accumulate Aβ oligomers/fibrils. We further found that recombinant human FAIM prevents the generation of pathologic Aβ oligomers and fibrils in a cell-free system, suggesting that FAIM functions without any additional cellular components. More importantly, recombinant human FAIM disaggregates and solubilizes established Aβ fibrils. Our results identify a previously unknown, completely novel candidate for understanding and treating irremediable, irreversible, and unrelenting neurodegenerative diseases.